Keeping it Safe: Space Heaters - Mary N. Harrison (EDIS, 2019)
Each year, hundreds of people go to hospital emergency rooms because of injuries related to space heaters. When clothing comes in contact with a heating element or flame it can catch fire. Leaking gas can cause explosions. Inhaling carbon monoxide from a malfunctioning, poorly vented, or unvented gas heater can cause death. This document is FCS5233-02, one of a series of the Department of Family, Youth and Community Sciences, UF/IFAS Extension. Original publication date: May 2002. Revised: December 2005.